Sms Gateway Untuk Pengembangan Sistem Antrian Pelayanan Kesehatan Gigi Di Klinik Assalam Medicare Surakarta - Amin, Siti Asiyah Fitria; , Sri Darnoto SKM., MPH (2017)
SMS Gateway is a system used to facilitate a person or a company to send the same SMS message at the same time in many people. This system has been widely used in various places including in health services. This study aims to implement SMS Gateway for the development of dental health service queue system at Assalam Medicare Surakarta Clinic. This type of research is a qualitative research with research and development design using prototype method through black box system test. Technique of data collecting by observation and interview to 11 informant representing executor of system, system operator and system user. The result of the research shows that the development of SMS Gateway system by mentioning the response SMS of the arrival time estimation for dental services at Assalam Medicare Surakarta Clinic is less precise due to unpredictable service action. Queuing of queuing at dental service of Assalam Medicare Surakarta Clinic is caused by many actions in patient which takes a long time for 1 hour so it looks queued because have to wait long for the next queue. But some ministry takes only 15 minutes for its actions. In performing the action the dentist should listen to the complaint and adjust to the patient's dental condition so that the timing of his actions can not be made on average and the waiting time of each patient is unpredictable. Implementation of SMS Gateway system with better time estimation applied in health service whose patient waiting time can be estimated, have registration officer who is able to understand IT and visiting patient can follow the system so SMS Gateway can be effective and efficient to be used as queuing system.